The sociology of education and work - Bills, David B., 1953- (Malden, MA : Blackwell Pub., 2004)
The Sociology of Education and Work is a clear and engaging study of the links between schooling and the workplace in modern society. It explains, in accessible and lively prose, how these links have developed over time, what broad social trends are transforming them now, and offers some empirically-based projections about how these relationships are likely to develop in the future. This book adopts a distinctly sociological perspective on these issues, while drawing on the disciplines of history, economics, demography, and policy analysis. It builds equally on the sociology of education and the sociology of work. Using a series of concepts and models including meritocracy, credentialism, post-industrial society, and the permanently new economy, this book encourages students to think about these issues sociologically. To bring life into these concepts, case examples are included to show the ways in which school and work come together in contemporary society. This book has brought together a wide body of literature for students studying education and work throughout the curriculum
Education and work: establishing some terrain -- Schooling and socioeconomic success: establishing their relationship -- Two models of the relationships between education and work -- Is the U.S. a meritocratic or a credentialist society? -- Education and work in the post-industrial society -- Demographic booms and busts, aging, and the new cultural diversity -- The transformation of the high school, the coming of mass higher education, and the youth labor market -- The possibilities of a learning society -- The future of education and work
Includes bibliographical references (pages 210-237) and indexes
Keywords: Education -- Social aspects -- United States; Work -- Social aspects -- United States; Educational sociology -- United States